Viral [large type] - Cook, Robin, 1940- (Thorndike Press large print core, 2021)
"Brian Murphy and his family are in Cape Cod when his wife, Emma, comes down with flu-like symptoms. But their leisurely return home to New York City becomes a race to the hospital as she begins seizing in the care. She is diagnosed with eastern equine encephalitis, a rare and lethal mosquito-borne disease. Complicating the situation further, Brian and Emma's daughter begins to exhibit alarming symptoms, too. Furious at the shockingly indifferent healthcare system, Brian vows to seek justice. But to get to the bottom of the predatory pricing targeting his loved ones, he must bring down the executives preying on the sick before the virus can claim even more people"--Page 4 of cover.